Some Evaluations on Open Soure E-learning Systems - Nguyen, Van Linh; Phan, Phuong Lan (Journal of Technical Education Science, 2009)
Researching and selecting a standard as well as a suitable learning management system (LMS) are two of the first tasks that we need do before developing an e-learning system. In this paper, we present standards in e-learning briefly. Besides, we also present the other authors’ research about open-source learning management systems. Basing on that study, we suggest that SCORM and Moodle should be used as a standard and a learning management system respectively.